Tonsillotomy for Periodic Fever Syndrome: A Randomized and Controlled Trial - Lantto, Ulla (WILEY, 2025)
Objective: Tonsillectomy is an effective treatment for periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome. Tonsillotomy has a milder operative risk profile and postoperative morbidity in children than tonsillectomy. We aimed to compare the efficacy of tonsillotomy to observation-only in children with PFAPA syndrome at a 3-month follow-up.
Methods: This was a randomized multicenter trial with sequential design. Participants were randomized into a tonsillotomy group and a control group that was only observed. The trial started in 1/2017 and was accomplished in 12/2021 with 16 patients (10 boys, six girls, the mean age 4.2 years). The symptoms were monitored with daily symptom diaries.
Results: After the 3-month follow-up, 7/8 patients (87.5%) in the tonsillotomy group and 2/8 (25%) patients in the control group were free from PFAPA symptoms (95% CI 13% to 87%; p = 0.0021). The mean number of days with fever was 2.6 (SD 3.7) in the tonsillotomy group and 8.0 (SD 6.5) days in the control group (n = 8) (p = 0.06). Mean number of fever days compatible with PFAPA syndrome was 0.8 (SD 1.4) in the tonsillotomy group and 6.5 (SD 6.0) in the control group (95%CI -10% to -1%; p = 0.007). Rescue tonsillectomy was needed for all patients in the control group and none of the patients in the tonsillotomy group.
Conclusions: Tonsillotomy might be an effective treatment option for children with PFAPA syndrome. Further studies are needed to clarify the long-term efficacy of tonsillotomy for treating PFAPA.